Caudal Extension Graft of the Lower Lateral Cartilage: Technique and Aesthetic and Functional Results - Sales, Juliano de Oliveira; Gubisch, Wolfgang; Duarte, Rodrigo Ribeiro Ferreira; Moreno, Aline Souza Costa Teixeira; Oliveira, Felipe Marques de; Coura, Lorena Martins de Oliveira (Facial Plastic Surgery, 2021)
Here we describe a new technique to deal with alar retraction, a highly undesirable imperfection of the nose. The procedure involves placing a caudal extension graft below the vestibular portion of the lower lateral cartilage (LLC) after its detachment from the vestibular skin. The graft is fixed to the cartilage and, subsequently, to the vestibular tissue. The present retrospective study included 20 patients, 11 females and 9 males, with a mean age of 28.90 years. Follow-up ranged from 1 to 18 months. Surgery improved alar notching to a smoother dome shape and nostril exposure was reduced in every patient. The caudal extension graft of the LLC contributed to rise in overall patient satisfaction, as revealed by the postoperative increase of the Rhinoplasty Outcomes Evaluation (ROE) mean score from 40.0 to 79.17 (p < 0.0001). It also contributed to and improved functional outcomes, as indicated by the decrease of the Nasal Obstruction Symptom Evaluation (NOSE) mean score from 52.75 to 13.25 (p = 0.0001). Sex did not affect the mean ROE and NOSE scores. Thus, increased patient satisfaction measured by the ROE is present in both sexes and at both age groups but it is better detected in the first year after surgery. Functional improvements analyzed with NOSE are best detected in patients aged ≥ 30 years and in follow-ups of 11 months. The caudal extension graft of the LLC technique described herein effectively and safely corrects alar retraction and the collapse of the nasal valve while filling the soft triangle.
Keywords: rhinoplasty; nasal cartilages; quality of life; nasal obstruction